Waste of Felling and On-Site Production of Teak Squarewood of the Community Forest - Ahmad Budiaman; Putri Komalasari (Institut Pertanian Bogor (IPB University), 2012)
Major suppliers of teak wood for the raw material of furniture industry in Indonesia are Perum Perhutani, community forests, and private forests. Community teak forest management produce roundwood or squarewood, in which squarewood is produced on the felling site by the use of chainsaw after felling and bucking activities. Utilization of teak wood from community forest has been practiced for decades, however information on the extent of utilization and the quantity of wood waste have not been published to a greater extent. The present research was intended to determine and analyze the extent of utilization and teak wood waste produced from felling and bucking, and on-site squarewood production of community forests. Quantification of wood waste from felling and bucking was based on the whole tree method, while that of squarewood production was based on the percentage of yield. It was found that the quantity of teak felling and bucking wood waste in community forest was reaching 28% of felled wood volume that consisted of branch and twig (46.15%), upper trunk (30.77%), short cut off (15.38%), and stumps (7.69%). The largest part of the wood waste of teak felling and bucking satisfied the requirement as raw material of wood working industry according to Indonesian National Standard. On-site production of squarewood increased the quantity of wood waste in the forests (in the form of slabs and sawdust).